4 - Carapa procera, femme et économie des ménages dans les communautés diola de la Basse Casamance, Sud du Sénégal - Diatta, Claudette Soumbane; Mbaye, Edmée; Diémé, Barnabé Ephrem A.; Diédhiou, Mamadou Abdoul Ader (Africa Development, 2024)
Women’s socio-economic conditions are often difficult in rural areas. In order to provide for their needs, this social category relies on the exploitation of part of the plant biodiversity. In Lower Casamance, the Carapa procera is one of these plants whose exploitation is culturally reserved for women but also improves their income and financial empowerment. This work highlights the cultural and economic implications of Carapa procera for women. To carry out this study, the sample size was determined using the DAGNELIE method. Two different questionnaires were administered to each target group. These questionnaires are completed by a focus group involving resource persons in the different localities of the study area. This approach yielded interesting results. Indeed, on the socio-cultural level, the study revealed that carapa provides through the mode of ownership, transmission and knowledge is considered by the communities as a heritage for women. Better still, in this difficult economic context, this heritage is an essential source of income for the women transformers. The exploitation of this heritage can bring them up to 250,000 CFA/year. This income is intended to cover household expenses, hence the importance of this species for the daily life of households, poverty reduction and the empowerment of women.